2013
DOI: 10.1097/01.ncn.0000432121.02323.cb
|View full text |Cite
|
Sign up to set email alerts
|

Text Messaging as Adjunct to Community-Based Weight Management Program

Abstract: Increasing obesity rates are still a public health priority. The primary aim of this study was to evaluate the effect of tailored text messages on body weight change in overweight and obese adults in a community-based weight management program. A secondary aim was to detect behavioral changes in the same population. The study design was quasi-experimental with pretest and posttest analysis, conducted over 12 weeks. A total of 28 participants were included in the analysis. Body weight, eating behaviors, exercis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 41 publications
0
31
0
Order By: Relevance
“…Moderate PA (min week −1 ) increased significantly in the majority of studies (9 out of a possible 13) and vigorous/hard/very hard PA increased significantly in 10 investigations (out of a possible 12). Six studies reported MET‐min week −1 of MVPA (4 reported means, 1 reported median, 1 reported least square mean); 3 reported MET‐min week −1 of moderate‐only PA and 3 reported MET‐min week −1 of vigorous‐only PA . On 5 (of a possible 8) occasions MET‐min week −1 of MVPA, 3 (of a possible 3) occasions MET‐min week −1 of moderate PA and 1 (of a possible 3) occasion MET‐min week −1 of vigorous PA increased following eHealth interventions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moderate PA (min week −1 ) increased significantly in the majority of studies (9 out of a possible 13) and vigorous/hard/very hard PA increased significantly in 10 investigations (out of a possible 12). Six studies reported MET‐min week −1 of MVPA (4 reported means, 1 reported median, 1 reported least square mean); 3 reported MET‐min week −1 of moderate‐only PA and 3 reported MET‐min week −1 of vigorous‐only PA . On 5 (of a possible 8) occasions MET‐min week −1 of MVPA, 3 (of a possible 3) occasions MET‐min week −1 of moderate PA and 1 (of a possible 3) occasion MET‐min week −1 of vigorous PA increased following eHealth interventions.…”
Section: Resultsmentioning
confidence: 99%
“…Studies included in the review were published between 2000 and 2016 and conducted in four high income OECD countries (USA = 44, Australia = 9, Canada = 3, United Kingdom = 4). Forty‐one RCTs ; 13 pre‐post ; 2 quasi‐experimental ; 1 randomized (no control) ; 1 ABA withdrawal design ; 1 within‐subjects trial and 1 prospective trial examined changes in MVPA levels following eHealth interventions. All papers were published in English.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A single administration of the instrument has been shown to distinguish the four subscales across different age groups and ethnicities, although most of these studies were conducted in college-aged samples (Byrd-Bredbenner, Quick, Koenings, Martin-Biggers, & Kattelmann, 2016; Schembre & Geller, 2011; Schembre, Nigg, & Albright, 2011). It has also been administered in short-term weight loss studies (Bouhaidar et al, 2013) twice within a short time range, but results from these longitudinal analyses were not reported. Therefore, the utility of the WREQ in identifying eating behaviors related to weight loss has not been demonstrated in the longer term.…”
Section: Introductionmentioning
confidence: 99%
“…Studies find that SMS-based reminders have led to improvements in applying sunscreen (Armstrong et al 2009), remembering to take diabetes drugs (Vervloet et al 2012), following HIV treatment regimens (Pop-Eleches et al 2011), adhering to asthma treatment (Strandbygaard et al 2010) and birth control pills (Castano et al 2012), getting vaccinated (Stockwell et al 2014), losing weight (Bouhaider et al 2013) and quitting smoking (Whittaker et al 2009). Because the health benefits of such behaviours may accrue well into the future, individuals may fail to follow through on intentions in the present, whether due to lack of attentiveness (Banerjee and Mullainathan 2008; Datta and Mullainathan 2014) or a bias towards alternative choices that may offer more immediate gratification (Strotz 1955; Ainslie 1975; Ainslie 1991; Hoch and Loewenstein 1991; Laibson 1997).…”
Section: Introductionmentioning
confidence: 99%